2011
DOI: 10.1111/j.1747-0803.2011.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Unrepaired Tetralogy of Fallot with Major Aortopulmonary Collateral Arteries in an Adult Patient

Abstract: Tetralogy of Fallot is characterized by a ventricular septal defect, a large, overriding aorta, subpulmonic stenosis, and right ventricular hypertrophy. These lesions can be associated with abnormal development of the pulmonary vasculature. This can include peripheral pulmonic stenosis, discontinuous pulmonary arteries, anomalous pulmonary venous return, and the development of aortopulmonary collateral vessels. Aortopulmonary collateral vessels develop to supply underperfused areas of the pulmonary bed and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…21 Tetralogy of Fallot with MAPCA is a complex form of cyanotic congenital heart disease that requires a comprehensive team-based assessment prior to surgical intervention. 22 Cardiac catheterization is usually essential to obtain all the necessary information. 19 Patients may occasionally present with multiple, large, unobstructed aortopulmonary collateral arteries producing excessive flow of blood to the lungs, and necessitating intervention.…”
Section: Discussionmentioning
confidence: 99%
“…21 Tetralogy of Fallot with MAPCA is a complex form of cyanotic congenital heart disease that requires a comprehensive team-based assessment prior to surgical intervention. 22 Cardiac catheterization is usually essential to obtain all the necessary information. 19 Patients may occasionally present with multiple, large, unobstructed aortopulmonary collateral arteries producing excessive flow of blood to the lungs, and necessitating intervention.…”
Section: Discussionmentioning
confidence: 99%
“…MAPCAs can develop in other conditions like TOF with pulmonary atresia and in this condition pulmonary circulation is dependent on these collateral [12]. MAPCAs can be an additional source of blood flow to lungs along with native pulmonary arteries like TOF with pulmonary stenosis [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Such repairs involve the closure of ventricular septal defect, relief of right ventricular outflow tract obstruction, maintenance of pulmonary valve competency when possible, and establishment of laminar pulmonary blood flow to all segments of the pulmonary bed. 10 In addition, it has been reported that the presence of foetal major aortopulmonary collateral arteries is associated with adverse outcome, therefore early diagnosis is essential. 11 In patients with pulmonary atresia and major aortopulmonary collateral arteries such as one reported in the present case, different surgical procedures are used as treatment.…”
Section: Discussionmentioning
confidence: 99%